2019
DOI: 10.1021/jacs.9b02947
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Rigidification for Enhancing the Stability of Metal–Organic Frameworks

Abstract: Metal–organic frameworks (MOFs) have been developing at an unexpected rate over the last two decades. However, the unsatisfactory chemical stability of most MOFs hinders some of the fundamental studies in this field and the implementation of these materials for practical applications. The stability in a MOF framework is mostly believed to rely upon the robustness of the M–L (M = metal ion, L = ligand) coordination bonds. However, the role of organic linkers as agents of stability to the framework, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
166
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(169 citation statements)
references
References 59 publications
2
166
0
1
Order By: Relevance
“…OMe‐TPBP‐COF displayed the highest thermal stability, followed by OMe‐OH‐TPBP‐COF and OH‐TPBP‐COF which might be attributed to the steric hindrance induced by the methoxyl substituents. Generally, the two phenyl rings in a biphenyl moiety readily rotate along the C−C bond, while the introduction of substituent at the 2,2’ ortho ‐positions can significantly limit the free rotation, thus enhancing the stability of the TPBP‐COFs . The steric hindrance of hydroxyl substituents is smaller than that of methoxyl groups, which leading to relatively poor stability of OH‐TPBP‐COF compared to OMe‐TPBP‐COF .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OMe‐TPBP‐COF displayed the highest thermal stability, followed by OMe‐OH‐TPBP‐COF and OH‐TPBP‐COF which might be attributed to the steric hindrance induced by the methoxyl substituents. Generally, the two phenyl rings in a biphenyl moiety readily rotate along the C−C bond, while the introduction of substituent at the 2,2’ ortho ‐positions can significantly limit the free rotation, thus enhancing the stability of the TPBP‐COFs . The steric hindrance of hydroxyl substituents is smaller than that of methoxyl groups, which leading to relatively poor stability of OH‐TPBP‐COF compared to OMe‐TPBP‐COF .…”
Section: Methodsmentioning
confidence: 99%
“…Generally,t he two phenyl rings in ab iphenyl moiety readily rotate along the CÀCb ond, while the introductiono f substituent at the 2,2' ortho-positions can significantly limit the free rotation, thus enhancing the stabilityo ft he TPBP-COFs. [28] The sterich indrance of hydroxyl substituents is smaller than that of methoxyl groups,w hich leading to relatively poor stability of OH-TPBP-COF compared to OMe-TPBP-COF. [29] Moreover,t he chemical stabilities of TPBP-COFs were tested by immersingt hese COF samples in boiling water,a queous NaOH (3 m)a nd HCl (3 m)s olutions for 3d ays.…”
mentioning
confidence: 99%
“…Here, we describe the preparation of NU-400 [43], a zirconiumbased MOF based on a judiciously chosen pyrene-based linker and utilized it as a photosensitizer for the efficient production of 1 O 2 and hence photocatalytic conversion of the sulfur mustard simulant 2-chloroethyl ethyl sulfide (CEES) into a benign sulfoxide product, using ambient air as the oxygen source. We selected a Zr 6 -based MOF because of its outstanding stability under a wide range of thermal and chemical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…S4). 45 The pore size analysis using DFT model revealed pores of approximately 11 Å, which is suitable for diffusion of CEES molecules into the pores of NU-400. Solid-state UV-Vis spectrum of NU-400 reveals that the strongest absorption bands lie below 400 nm (see Fig.…”
mentioning
confidence: 97%
“…1) was synthesized from the 2,7-pyrenedicarboxylic acid (Py-DCA) linker, ZrCl4 metal salt, and acetic acid as a modulator, in DMF at 120 ℃ (see S.3 for synthetic details). Different from the reported synthesis of 2,7-pyrene dicarboxylic acid linker, 45 which required an organolithium reagent, a more benign Pd-catalyzed carbonylation reaction was utilized with 2,7-dibromopyrene as the starting material. 46 Powder X-ray diffraction (PXRD) analysis of the as-synthesized materials revealed that NU-400 is isostructural to the related UiO-67 framework based on 4,4'-biphenyldicarboxylate linkers.…”
mentioning
confidence: 99%